Modelo gerencial de mensuração do portfólio de patentes de um centro de pesquisa e desenvolvimento em telecomunicações - Adriano, Eunice (2014)
The goal of this work is to propose a model for management measurement for the patent portfolio owned by a center for research and development in telecommunications. It features the concept of intellectual property, as it considers that seeing knowledge as a strategic tool for the organizations and the use they make of it in society show how important the information sector is for the economy of all countries. By presenting the question of patents and their value, it shows that building value and generating wealth is the ultimate foundation of Economic Science. As it proposes a model for analyzing the portfolio of patents, it rests on the assumption according to which a rational exploration of its protected patents will allow for a fair compensation for the efforts exerted and to recoup the investments incurred during the research. The work required for determining the valuation of a patent involves procedures similar to those deployed for analyzing any other types of ownership, that is, it is necessary to check if there are co-owners, the useful life of the patent, the cost of maintaining it, the objective of the patent holder as regards exploiting it, and which economic benefits are expected concerning the amount of return, time span covered and the risk associated with deriving those benefits, which would warrant identifying it as an intangible asset of one organization. We then focus attention on methods that can be used to determine the value of patent based in monetary benefits. The patent portfolio of a corporation may generate a significant value as long as it identifies valuable patents that do not afford adequate protection or those whose maintenance fees are not worth the cost.